Active Media Perfusion in Bioprinted Highly Concentrated Collagen Bioink Enhances the Viability of Cell Culture and Substrate Remodeling - Kanokova, Denisa; Matejka, Roman; Zaloudkova, Margit; Zigmond, Jan; Supova, Monika; Matejkova, Jana (Gels, 2024)
The bioprinting of high-concentrated collagen bioinks is a promising technology for tissue engineering and regenerative medicine. Collagen is a widely used biomaterial for bioprinting because of its natural abundance in the extracellular matrix of many tissues and its biocompatibility. High-concentrated collagen hydrogels have shown great potential in tissue engineering due to their favorable mechanical and structural properties. However, achieving high cell proliferation rates within these hydrogels remains a challenge. In static cultivation, the volume of the culture medium is changed once every few days. Thus, perfect perfusion is not achieved due to the relative increase in metabolic concentration and no medium flow. Therefore, in our work, we developed a culture system in which printed collagen bioinks (collagen concentration in hydrogels of 20 and 30 mg/mL with a final concentration of 10 and 15 mg/mL in bioink) where samples flow freely in the culture medium, thus enhancing the elimination of nutrients and metabolites of cells. Cell viability, morphology, and metabolic activity (MTT tests) were analyzed on collagen hydrogels with a collagen concentration of 20 and 30 mg/mL in static culture groups without medium exchange and with active medium perfusion; the influence of pure growth culture medium and smooth muscle cells differentiation medium was next investigated. Collagen isolated from porcine skins was used; every batch was titrated to optimize the pH of the resulting collagen to minimize the difference in production batches and, therefore, the results. Active medium perfusion significantly improved cell viability and activity in the high-concentrated gel, which, to date, is the most limiting factor for using these hydrogels. In addition, based on SEM images and geometry analysis, the cells remodel collagen material to their extracellular matrix.